Analisis Kompetensi Profesional Guru IPS SMP Bersertifikasi Tahun Ajaran 2018/2019 - Much Enandang; Sumadi Sumadi; Zulkarnain Zulkarnain (JPG (Jurnal Penelitian Geografi), 2019)
This research aims to analyse the professional competence through the Analysis of Certified Junior High School Social Science Teachers in Metro City Academic Year 2018/2019. in which the results as the following, 1) the mastery related to material, structure, concept, and mind set of social science has a good percentage (83.4%), 2) the use of technology, information and communications technology (ICT) to improve the learning quality of social science shows a good percentage (76.1%), 3) the use of objective to improve the learning quality has a good percentage (78.1%), 4) the philosophy, methodology, technical, and praxis masteries have a good percentage (88%), 5) the self expanding of professional performance has a good percentag (85.7%), 6) improving performance and commitment to society devoting have a good percentage (80.9%). Penelitian ini bertujuan untuk menganalisis kompetensi profesional pada Analisis Kompetensi Profesional Guru IPS SMP Bersertifikasi di Kota Metro Tahun Ajaran 2018/2019. di dapat hasil presentase (1) penguasaan materi, strukur, konsep dan pola pikir ilmu pengetahuan sosial (IPS) dengan presentase baik (83,4%).(2) pemanfaatan teknologi informasi dan komunikasi (TIK) untuk meningkatkan kualitas pembelajaran ilmu pengetahuan sosial (IPS) menunjukan presentase baik (76,1%). ( (3) pemanfaatan tujuan untuk meningkatkan kualitas pembelajaran dengan presentase baik (78,1%).(4) Menguasai Filosofi, Metodologi, teknis, dan Praksis presentase baik (88%). (5) Mengembang diri dari kinerja professional presentase baik (85,7%).(6) Meningkatkan Kinerja dan Komitmen Pengabdian Kepada Masyarakat presentase baik (80,9%).Kata kunci: bersertifikasi, guru, profesional